2019
DOI: 10.1093/jas/skz258.790
|View full text |Cite
|
Sign up to set email alerts
|

PSIX-10 The replacement of corn by soybean molasses improves ruminal environment of feedlot sheep

Abstract: The goal of this study was to assess the effects of increasing levels of soybean molasses (SM) on ruminal parameters of feedlot sheep. Nine crossbred ruminally-cannulated male sheep (73.3 ± 2.5 kg BW) were randomly distributed in a triple 3 × 3 Latin square design. The treatments consisted of isonitrogenous (18% CP) and isoenergetic (2.7 Mcal/kg) diets, containing 0, 15 or 30% SM (DM basis). After 14 d of adaptation period, rumen fluid samples were collected in each experimental period, at 0, 2, 4, 6, 8 and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…On the hand, the lower fiber content in the SM20 diet did not seem to affect ruminal pH, as indicated by the higher muscle content of stearic acid (C18:0), the content of which is narrowly linked to biohydrogenation in the rumen ( Santos-Silva et al, 2016 ). Agreeing with this, SM inclusion up to 30% in the diet of adult sheep directly increased ruminal pH ( Pereira-Junior et al, 2019 ). Another indicatives of good ruminal biohydrogenation capacity are the similar levels of PUFA and higher amounts of SFA and some MUFA in the muscle of SM20 lambs, despite the presence of 45% and 51% of PUFA in CON and SM20 diets, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…On the hand, the lower fiber content in the SM20 diet did not seem to affect ruminal pH, as indicated by the higher muscle content of stearic acid (C18:0), the content of which is narrowly linked to biohydrogenation in the rumen ( Santos-Silva et al, 2016 ). Agreeing with this, SM inclusion up to 30% in the diet of adult sheep directly increased ruminal pH ( Pereira-Junior et al, 2019 ). Another indicatives of good ruminal biohydrogenation capacity are the similar levels of PUFA and higher amounts of SFA and some MUFA in the muscle of SM20 lambs, despite the presence of 45% and 51% of PUFA in CON and SM20 diets, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…The high solubility of soluble carbohydrates in SM allows for easy escape of microbial fermentation, resulting in the conversion of protein and non-protein nitrogen into ammonia in the rumen, and this, in turn, into urea by the liver ( Hailemariam et al, 2021 ). Pereira-Junior et al (2019) , when evaluating inclusions of up to 30% of SM in DM, found a reduction in ruminal NH 3 , indicating greater epithelial absorption. In turn, our current study found higher levels of urea in the blood, indicating high activity in the urea cycle.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, feed digestibility, feed consumption behavior, and metabolic profile of sheep were not affected, indicating that soybean molasses can be used successfully as a feed ingredient for sheep until 12% of the daily ration without any risk of intoxication. The influence of soybean molasses on the ruminal environment has been also investigated [ 67 , 68 , 69 , 70 , 71 ]. Sheep diet containing 0%, 15%, or 30% soybean molasses (dry matter basis) increased proportionally ruminal pH and decreased NH3-N concentration, thereby improving the ruminal fermentation.…”
Section: Soybean Molasses In Animal Feed Productionmentioning
confidence: 99%